Pelaksanaan Belajar dari Rumah pada Pembelajaran Bola Voli - Retno Dwi Hartanti; Resty Gustiawati; Abduloh Abduloh (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research was motivated by the author's interest in the implementation of learning from home in class XI volleyball learning at SMAN 1 Banyusari. The implementation of learning from home (BDR) is a method of learning from home for learners to still get education during the covid-19 pandemic. The goal is to find out how the process in the implementation of learning from home on volleyball learning in the current pandemic period. This study uses survey methods with a quantitative approach. This data collection technique uses a statement instrument in the form of a questionnaire with data analysis techniques using deskrtiptive statistics with percentages. The population in this study is a student of SMAN 1 Banyusari class with using Random Sampling Techniques and respondents of 35 students. Based on the results of research and money information provided so that the minimum value = 235, maximum value = 520, average value = 370, standard deviation = 67.68 and concluded that the implementation of learning from home on volleyball learning category "very low" 7 respondents with a percentage of 20%, "low" category 3 respondents with a percentage of 8.57%, category "medium" 2 respondents with a percentage of 5.71%, category "high" 0 respondents, category "very high" 23 respondents with a percentage of 65.71%